Evaluation of Risk Factors in Caries Formation in Children - Kuter Berna; Atesci Alp Abidin; Uzel İlhan (Balkan Stomatological Society, 2020)
Background/Aim: The aim of this study was to evaluate the risk factors in caries formation and relationships between each other in children.